Techno-economic feasibility of tomato (Solanum lycopersicum) hybrids for year-round cultivation in Andamans, India (Current Horticulture, 2024)
The experiment was conducted to investigate adaptation of tomato (Solanum lycopersicum L.) hybrids in different growing condition in tropical island and assess the techno-economic feasibility for year-round cultivation at CIARI, Port Blair, Andaman and Nicobar Islands, India during 2012-13 and 2013-14. Seven hybrids and three varieties were evaluated in three growing environments (open+dry season, open+rainy season and polyhouse+rainy season). Arka Rakshak (369.3 q/ha), Ayushman (351.6 q/ha) and Arka Samrat (339.3 q/ha) were consistent performer all the conditions with highest yield levels and they also had low incidence of bacterial wilt,i.e. 34.2%, 29.2% and 33.3%, respectively. Risk analysis using Likert scale score revealed that heavy rains, lack of suitable varieties and bacterial wilt are major risk in farmers' view. Accordingly, they ranked techno economically feasible options and prominent were varieties/hybrids, polyhouse technology, grafting and raised beds for year-round production. The study will ensure year-round production of tomato locallyand also prospective areas of research for tomato cultivation in tropical islands.
Keywords: Economic feasibility; F1 hybrids; High-value vegetables; Tropical islands